The relationship between mathematics excellency and efficiency of accounting students - Zandi Pour Joopari, GholamReza; Shahabi, Alireza; Bagheri, Mojtaba (David Publishing, 2012)
Many organizations, educational institutes, and universities wish to identify efficient and high caliber applicants who could excel over the accounting discipline, while scholarships and admissions are still not offered. However, it is believed that undergraduate accounting students with majors in mathematics from pre-university institutes perform much better than those with arts or social sciences backgrounds. Therefore, this paper1 takes the mathematics perception level as well as pre-university’s cumulative grade point averages (CGPAs) as the main indicators of efficiency and better performance of undergraduate accounting students. In order to test the hypotheses, a multiple regression analysis has been used. By choosing all undergraduate accounting candidates, who had been admitted for academic calendars of 2009-2010 in four different universities (one public, two semi-publics, and one private university) and testing their mathematics excellency, as well as extracting their CGPAs, the authors find that students’ mathematical talents are high, and to a lower extent, the CGPAs will positively influence the performance in accounting courses.